ANALISIS PEMBELAJARAN EDUTAIMENT - Jessica Tri Agustini; Dzikra Asy-Syifa; Asiyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Edutainment learning is present as a response to the low motivation and high boredom of students in the conventional learning system that is still dominant in Indonesia. This study aims to analyze the concept, characteristics, objectives, theoretical basis, as well as the advantages and disadvantages of the edutainment learning model in the context of modern education. The method used is library research by reviewing various relevant scientific literature, such as books, journals, and academic articles. Data is analyzed qualitatively through a descriptive-analytical approach to obtain a comprehensive understanding of the implementation of edutainment in learning. The results of the study show that edutainment has the main characteristics of humanizing the classroom, the use of interactive multimedia media, adaptive flexibility, and the application of formative evaluation. This model is supported by constructivism theory, flow theory, and multimedia learning theory which emphasizes the active involvement of students and optimal management of cognitive load. The advantages of edutainment lie in its ability to increase intrinsic motivation, knowledge retention, and a pleasant learning atmosphere. However, implementation challenges include limited teacher creativity and supporting facilities, as well as the risk of learning becoming too entertainment-oriented if not designed appropriately